2018
DOI: 10.1186/s13071-018-3201-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal heterogeneity in malaria receptivity is best estimated by vector biting rates in areas nearing elimination

Abstract: BackgroundDecisions on when vector control can be withdrawn after malaria is eliminated depend on the receptivity or potential of an area to support vector populations. To guide malaria control and elimination programmes, the potential of biting rates, sporozoite rates, entomological inoculation rates and parity rates to estimate malaria receptivity and transmission were compared within and among geographically localised villages of active transmission in the Western Province of the Solomon Islands.ResultsMala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 36 publications
1
59
0
1
Order By: Relevance
“…Therefore, the EIR evaluated during this study should be interpreted with caution, as the level of exposure to Anopheles during the day and the night is very low. Nevertheless, this study shows the importance of maintaining a continues entomological surveillance during the whole year in areas dealing with low level of exposure to vector bites and residual malaria transmission [24,25]. However, incorporating a sociodemographic aspect into control strategies could help to provide better containment for residual transmission as human behaviour contributes greatly to malaria outbreaks in this situation [3,26] and malaria transmission could persist at very low level even during the dry season [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the EIR evaluated during this study should be interpreted with caution, as the level of exposure to Anopheles during the day and the night is very low. Nevertheless, this study shows the importance of maintaining a continues entomological surveillance during the whole year in areas dealing with low level of exposure to vector bites and residual malaria transmission [24,25]. However, incorporating a sociodemographic aspect into control strategies could help to provide better containment for residual transmission as human behaviour contributes greatly to malaria outbreaks in this situation [3,26] and malaria transmission could persist at very low level even during the dry season [27].…”
Section: Discussionmentioning
confidence: 99%
“…Also, important to highlight, is that the key vector indicators to be monitored will change as transmission intensity diminishes and the range of available recommended interventions increases. While sporozoite rates are a recommended key indicator in high transmission scenarios, the value of sporozoite and entomological inoculation rates to guide programmatic decisions wanes with the need to measure biting rates becoming an increasingly important indicator for predicting transmission risk [44].…”
Section: Algorithms For Representative Samplingmentioning
confidence: 99%
“…Resurgence of malaria is often associated with imported infections and/or P. vivax relapsing infections in areas that remain highly receptive to malaria [13][14][15][16]. Studies have demonstrated the usefulness of spatially referenced entomological data to characterise the heterogeneity of malaria receptivity in areas approaching elimination to prevent outbreaks in the future [17][18][19]. However, entomological surveillance can often be logistically challenging in low transmission areas due to the difficulty of catching meaningful numbers of mosquitoes.…”
Section: Introductionmentioning
confidence: 99%